UPAYA MENINGKATKAN KETERAMPILAN MENGAJAR GURU MELALUI TEKNIK TEAM TEACHING METHOD (TTM) DI SD NEGERI KEMBANGLIMUS - Genduk Widayati (Jurnal Inovasi Pendidikan dan Teknologi Informasi (JIPTI), 2023)
Teachers can be said to be professional if they have expertise in their field, namely mastery of the material being taught and methods of teaching. Therefore, teachers must understand and practice basic teaching skills. This skill makes learning better and more effective so that it is easy for teachers to get to know students more deeply and students easily understand the material that has been given. However, in terms of quality, what is expected of a skilled teacher in teaching is still far from expectations. To overcome this problem, a classroom action research (CAR) was conducted using the Team Teaching Method technique. The purpose of this study was to improve teaching skills for teachers at SD Negeri Kembanglimus, Borobudur District, for the 2021/2022 academic year using the Team Teaching Method technique. The research subjects were 8 teachers. The source of the research data was obtained from qualitative data in the form of data from observations of teacher activities, quantitative data in the form of the results of improving teacher skills in teaching. The results of the first cycle of research from 8 teachers who participated in the Team Teaching Method activities with a discussion of teaching skills, there were 3 teachers in the very good category, 3 teachers in the good category, and 2 teachers in the moderate category. On average, the teacher's teaching skill score at SD Negeri Kembanglimus, Borobudur District, Magelang Regency after the implementation of the Team Teaching Method activity cycle 1 was in the good category. These results indicate that the Team Teaching Method activities are going well so that they have a positive impact on the results, namely improving teacher teaching skills. While the results of the second cycle research experienced an increase of 8 teachers participating in the Team Teaching Method activities with a discussion of teaching skills, there were 7 teachers with very good category, and 1 teacher with good category. On average, the teacher's teaching skill score at Kembanglimus Public Elementary School, Borobudur District, Magelang Regency after the implementation of the Team Teaching Method activity cycle 2 was in the very good category. These results indicate that the Team Teaching Method activities are going well so that they have a positive and effective impact on the results, namely improving teacher teaching skills.